Comparison of the relationship among three major pests and multiple natural enemies in tea garden - DANG Feng-hua; GONG Mao-lian; BI Shou-dong; ZOU Yun-ding; XU Zeng-en (浙江大学学报. 农业与生命科学版, 2010)
To determine the major natural enemies of pests, the tea pests and their natural enemies were investigated systematically, and the survey data of the pests and natural enemies were further studied using grey correlation analysis, ecological niche analysis and spatial pattern of aggregation intensity index analysis to identify the major kinds of major pests in Jianghuai hilly tea plantation. The synthetic ranking result indicated that the main natural enemies of Empoasca vitis were Theridion octomaculatum, Tetragnatha maxillosa and Xysticus ephippiatus; the main natural enemies of Toxoptera aurantii were Propylaea japonica, Harmonia axyridis and Mantis religiosa; and the main natural enemies of Pealius akebiae were Neoscona theis, Chrysopaseptempunctata and Harmonia axyridis. Gathering averages of E. vitis and P. akebiae of major three pests were greater than two due to the aggregated nature of the insect, while that of T. aurantii was less than two due to the certain environmental factors.